Analysing Web Traffic A Case Study on Artificial and Genuine Advertisement-Related Behaviour - Jastrzębska, Agnieszka; Owsiński, Jan W.; Opara, Karol; Gajewski, Marek; Hryniewicz, Olgierd; Kozakiewicz, Mariusz; Zadrożny, Sławomir; Zwierzchowski, Tomasz (Studies in Big Data, 2023)
XX, 156 p. 95 illus., 90 illus. in color.